The Perceptions of Pre-Service Science Teachers and Science Teachers about Climate Change - Meilinda, M.; Rustaman, N. Y.; Tjasyono, B. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
The global climate phenomenon in the context of climate change is the impact of both the dynamic complex climate system and human behaviors that affect environmental sustainability. Human is an important component that should be considered in science teaching that is believed to improve human attitudes towards the environmental sustainability. The research aims to investigate the perceptions of pre-service science teachers and science teachers in South Sumatra who teach climate change and global warming. The data were collected from 17 science teachers and 53 pre-service science teachers from April to August 2016. The instruments were 17 modified questions which were developed from Pruneau’s framework. There are three linear perceptions regarding climate change. First, greenhouse effect causes global warming and global warming causes climate change. Second, ozone leakage causes global warming and global warming causes acid rain. Third, greenhouse effect causes ozone leakage and ozone leakage causes global warming; then it causes climate change and other climatic phenomena. Both pre-service science teachers and science teachers argue that climate change is caused by global warming. Actually, climate change is not only global warming but also global cooling. Those phenomena occur because of interactions among climate system components. They do not believe that education is able to change human attitudes in saving environmental sustainability from global climate change disasters. They believe that media give stronger effects than teachers in shaping those perceptions. Factually, most of wrong perceptions come from media.